Negara Islam V.S. Negara Yahudi Analisis atas Alasan-alasan Pehdirian Negara dalam Islam dan Yahudi - Agus Triyanta (Jurnal Hukum IUS QUIA IUSTUM, 2002)
In the modem age like this time, where secularization have penetrated in any human's views, but turn out the rest of people have not been destructed by secularization, including here is the view of compulsory forregulating political state with the religious Institution in the Moslem and Jew communities. These writings are going to explain the problem of reason for establishing Islamic and Jew States.